Dense fog disaster management: Systematic literature review - Kyoo-Man Ha (Transportation Research Interdisciplinary Perspectives)
Even though dense fog leads to cascading disasters, many communities worldwide still focus on how to improve transportation during its occurrence. This study examined ways to enhance the emergency response phase during a thick fog to reduce the associated physical and social impacts. A systematic literature review was employed as the primary method. To develop response-phase-oriented dense fog disaster management, international organizations, disaster management agencies, regional climate institutions, and other local communities initially explored the feasibility of safe-driving-oriented dense fog disaster management. It was found that these four stakeholders would facilitate the advantages of emergency response, an all-hazards strategy, culture and sustainability, psychology and warfare, and education and training while transforming the safe-driving-oriented approach into an emergency response-oriented approach. This study comprehensively incorporated minority perspectives into emergency response, particularly for researchers and traffic professionals.